Communication range extending PSK backscatter modulation in passive RFID - Evecan, Kazım (Graduate School, 2024)
In this study, analyses and simulations to increase the communication distance of passive RFID systems in forward and reverse directions have been carried out through equations. All modulation techniques have been compared fairly with the equations obtained by classical circuit theory and based on the power of the RFID tag and reader. It has been shown that the time at which the average peak power consumption of the tag occurs during communication affects the communication distances. After using the parameters determined by the regulatory institutions and obtained from the literature, the free parameters on the system were obtained by keeping any parameter constant, and thus concrete data was obtained. The results were further confirmed using data from recent studies found in the literature with tag threshold power between 664 nW and 1 μW. It was concluded that the performance of binary phase shift keying modulation is better than amplitude shift modulation in terms of communication distance, signal-to-noise ratio or bit error rate, and receiving antenna gain. Long communication distance is important in environments where there are many obstacles and noise, as it enables the tag to work successfully. The long communication distance feature can be transformed into a receiving antenna that can be used in smaller sizes and at less cost. Similarly, it also provides more reliable communication with a higher signal to noise ratio or less bit error rate at the receiving end. It has now been observed that the communication distance of RFID systems has begun to be limited by backward communication rather than forward communication, which provides energy and information. This situation shows that it will be necessary to switch to a bistatic antenna configuration for the reader instead of a monostatic antenna configuration. Equations have been put forward that the reader configuration change is mandatory for the given parameters after the power of the tag exceeds a threshold level. It has been concretely demonstrated by equations that phase shift modulation has the potential to increase speed. This potential can be implemented without changes from the EPC Class I Gen II rules and generally without changes in communication distance. Depending on the time at which the average peak power consumption on the tag occurs during communication, increasing the speed may require sacrificing some communication distance. Phase shift keying modulator varactor size reduction opportunity has been shown by equations to shrink die area. Depending on peak power consumption during communication, it can be exploited completely or partially.
Pasif RFT için iletişim mesafesini arttıran faz kaydırmalı geri saçılma kiplenimi
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2024
Keywords: RFID; RFT; Antenna Design; Anten Tasarımı; Communication distance; İletişim mesafesi